Pemahaman Masyarakat terhadap Nusyuz dan Dampaknya terhadap KDRT dalam Rumah Tangga - Nurzakia . (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Islam regulates the resolution of nusyuz (disobedience) for husbands and wives in the Qur'an Surah an-Nisa’ verse 34 and an-Nisa’ verse 128. Within the Islamic law, the resolution of nusyuz does not promote any violence against wives. Beatings to wives as stated in Surah an-Nisa’ verse 34 should be interpreted as actions to give lessons. However, some cases of domestic violence, relate to the understanding of nusyuz developed within the community. People generally understand nusyuz as an act of a wife's disobedience towards her husband. This inaccurate understanding of nusyuz may lead to domestic violence by the husband, under the pretext of a disobedient wife, while most often it is the husband who is disobedient. In this present study, the field research approach was used. The data collection techniques included interviews and documentation. The data were then analyzed using the qualitative descriptive analysis by interpreting and describing the data. The results of the study revealed that there were three groups of people that understood the concept of nusyuz differently at Ingin Jaya Subdistrict of Aceh Besar District. The first group perceived that nusyuz could be present both in the wife and in the husband. The second group argued that the nusyuz attitude only existed within the wife, whereas the third group had no idea of the concept of nusyuz at all even though they might have done it. The public understanding of nusyuz is very likely obtained from their educational background. Those studying in Islamic boarding schools have had more knowledge of religion and vice versa. Here, most of the interviewees stated that the concept of nusyuz was closely related to domestic violence because public perception had been highly influenced by Surah an-Nisa’ verse 34 concerning the beating of a nusyuz wife. This perception has then given the husband a valid reason to physically beat the wife who has been considered nusyuz. Thus, it is difficult to separate the Islamic doctrine that has long developed within the lives of today’s Muslim communities.